EVALUATION OF OXIDATIVE STRESS, ANTIOXIDANT DEFENSES, AND BIOCHEMICAL DYSREGULATION IN OBESE VS. NON-OBESE ADULT MALES - Adil, Sozdar A; Mohammed, Lina Y (Science Journal of University of Zakho, 2025)
Obesity is a major public health concern linked to metabolic disturbances and increased oxidative stress. The objective of this research is to evaluate the effect of obesity on oxidative–antioxidant balance in adult males. Comparative cross-sectional study was done at Zakho General Hospital, Iraq, from October 2024 to January 2025, involving 90 males aged 18–44 years, distributed into obese body mass index (BMI) ≥30 and non-obese body mass index (BMI) <25 groups. Blood samples were collected and analyzed for biochemical, and oxidative stress parameters using Cobas auto-analyzers and spectrophotometric methods. Obese individuals exhibited significantly higher body mass index (BMI), waist circumference (WC), diastolic blood pressure (DBP), fasting blood glucose (FBG), fasting insulin (FI), lipid profile, Liver enzymes (aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and gamma-glutamyl transferase (GGT)), Kidney function parameters (urea, creatinine and uric acid), High-sensitivity C-reactive protein (hs-CRP) and homeostatic model assessment of insulin resistance (HOMA-IR) in comparison with controls. Concentrations of Zinc (Zn) and copper (Cu) were elevated, whereas magnesium (Mg) was decreased in the obese group. Antioxidant markers (glutathione S-transferase (GST), superoxide dismutase (SOD), and catalase) were significantly reduced in obese group. Strong negative correlations are observed between oxidative markers and most anthropometric and biochemical parameters. Obesity in adult males is associated with impaired antioxidant defense and alterations in trace elements, emphasizing the oxidative stress burden in obese individuals and the need for early preventive strategies